THE EFFECT OF TASK COMPLEXITY ON QUALITY OF AUDITOR’S WORK: THE IMPACT OF ACCOUNTABILITY AND KNOWLEDGE - RIA NELLY SARI; DIANI MARDISAR (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
The study examines the effect of accountability and knowledge on auditors’ performance (quality of auditor’s works). It is expected that the degree of task complexity (low and high complexity task) has different effect on quality of auditors’ work. It is also predicted that knowledge moderate the relationship between accountability and quality of auditors’ work. Data was obtained from auditors who work for local Accounting Public Firm in Pekanbaru and Padang. A total of 62 responses (44.29%) was accepted and used in the analysis. Data is analyzed by using multiple regression. Results of the study indicate that when task complexity is low, accountability will effect quality of auditor’s work, but when task complexity is high, accountability does not have effect on quality of auditor’s work. In addition, when task complexity is high, interaction between accountability and knowledge has significant influence on quality of auditor’s work. Suggestions for future research are also given to address the present study’s limitation.